Variasi Dimsum Hakau Udang dengan Bumbu Rendang di Pabrik Dimsum 220 - Siti Nuning Nuriah; Siti Nurrahmi Unayah (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This research discusses the development of the Hakau Shrimp Dimsum product with Rendang Seasoning, which aims to add variety to Dimsum 220 which usually uses chili sauce plus rendang seasoning. The method used in this research is research and development, by carrying out a series of experiments and developments using a hedonic scoring scale test involving twenty-five panelists. Based on the results of the research that has been carried out, it can be seen that the overall calculation results for the level of liking obtained an appearance value of 60% very like and 40% like. 40% really like the color and 60% like it. 80% really like the texture and 20% like it. 68% really like the aroma and 32% like it. 100% really like it. The standard recipe for this product consists of tang mien flour, shang fhen flour, shrimp, chicken skin, tapioca flour, margarine and rendang seasoning. Business analysis shows a profit of IDR 3,000,000 from sales of 2,898 pcs/month. This research recommends that innovation in dimsum products can continue to be developed following market developments.